Usulan Perencanaan dan Pengendalian Persediaan Bahan Baku Menggunakan Metode Lot Sizing pada Pabrik Mebel - Mirna Lusiani; Willy Sandi (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This research discusses the planning and inventory control of raw materials in PT Rackindo Setara Perkasa which is one of the manufacturer in Indonesia which is engaged in the industry of knock-down furniture. The purpose of this study is to planning and controlling the inventory of raw materials with the lowest cost. The research is conducted to develop demand forecast in 2016, to develop the aggregate planning using LINGO software, then continued in the design of the Master Production Schedule (MPS) and Material Requirement Planning (MRP). This research discusses the comparison of several methods of Lot Sizing in MRP, such as the Economic Order Quantity (EOQ), Period Order Quantity (POQ) and Least Total Cost (LTC). The selected Lot Sizing method is a method with the lowest inventory cost.Keywords: Inventory Control, Forecasting, Aggregate Planning, Lot Sizing, Master Production Schedule, Material Requirement Planning